Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Federal Internasional Finance Cabang Taman Palem Cengkareng - Gloria, Putri; Firdaus, Ahmad; Sambo, Andarias (Journal MISSY (Management and Business Strategy), 2025)
This study aims to analyze the influence of Leadership Style, Work Motivation, and Work Discipline on Employee Performance at PT Federal International Finance, Taman Palem Cengkareng Branch. The research employed a quantitative method with a population of 150 employees and a sample of 60 respondents determined using the Slovin formula. Data analysis was conducted using the Partial Least Square (PLS) application. The results show that Leadership Style has a negative and insignificant effect on Employee Performance, with a t-statistic value of 1.298 < 1.967 and a P-value of 0.195. Conversely, Work Motivation has a positive and significant effect on Employee Performance, with a t-statistic of 3.048 > 1.967 and a P-value of 0.002. Similarly, Work Discipline has a positive and significant effect on Employee Performance, with a t-statistic of 4.425 > 1.967 and a P-value of 0.000. Thus, Work Motivation and Work Discipline are proven to be the dominant factors in improving employee performance.